Experience of double balloon enteroscopy. Issue 3 (March 2018) - Su, Ming‐Yao; Lin, Wei‐Pin; Chiu, Cheng‐Tang
Abstract : Background: : To evaluated the experiences of double balloon enteroscopy (DBE) for obscure gastrointestinal bleeding. Methods: : From October 2003 to November 2009, a total of 124 patients with obscure gastrointestinal bleeding were investigated using DBE. A total of 142 procedures (84 per oral and 58 per rectal route) were performed by the same endoscopist. Results: : The average insertion time was 71.4 (20–199) minutes per‐orally; the average insertion time was 139.2 min for the first 5 procedures, 109.4 min for 6–10 procedures, 76.6 min for 11–15, 66.4 min for 16–20, 67.4 min for 21–25, 59 min for 26–30, 66 min for 31–35, 52 min for 36–40, 42.9 min for 41–45, 44.6 min for 46–50, 42.2 min for 51–55, 38.6 min for 56–60, 44.6 min for 61–65, 37.8 min for 66–70, 38.8 min for 71–75, 44.3 min for 76–80, and 36.6 min for 61–84 procedures; there was no statistical difference after the first ten procedures. The average insertion time was 92.1 (22–260) minutes per‐rectally; the average insertion time was 159.6 min for the first 5 procedures, 98.4 min for 6–10 procedures, 86.6 min for 11–15, 76.4 min for 16–20, 82.4 min for 21–25, 75.0 min for 26–30, 78.2 min for 31–35, 72.4 min for 36–40, 68.2 min for 41–45, 66.9 min for 45–50, and 71.4 min for 51–58 procedures; there was no statistical difference after the first five procedures. For the different genders these was no statistically significant difference. There were no differences regarding the diagnostic yield between the previous factors. The overall diagnostic yield was 82.4%. Conclusion: : DBE is a safe and effective means of diagnosing and managing patients with obscure gastrointestinal bleeding. However, because of its time‐consuming, DBE has a learning curve to overcome before a physician can become an expert to achieve adequate insertion times with good diagnostic and therapeutic rates.